Information provision over the phone saves lives: An RCT to contain COVID-19 in rural Bangladesh at the pandemic's onset - Shyamal K. Chowdhury; Hannah Schildberg-Hörisch; Sebastian O. Schneider; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2022)
Lack of information about COVID-19 and its spread may have contributed to excess mortality at the pandemic's onset. In April and May 2020, we implemented a randomized controlled trial with more than 3,000 households in 150 Bangladeshi villages. Our one-to-one information campaign via phone stressed the importance of social distancing and hygiene measures, and illustrated the consequences of an exponential spread of COVID-19. We find that information provision improves knowledge about COVID-19 and induces significant behavioral changes. Information provision also yields considerably better health outcomes, most importantly by reducing the number of reported deaths by about 50% in treated villages.
hdl:21.11116/0000-000B-9C68-1
Keywords: C93; D01; D91; I12; 330; Field experiment; COVID-19; Information intervention; Death rates